2008
DOI: 10.1196/annals.1448.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cell‐Free DNA of Patients with Cardiomyopathy and rDNA on the Frequency of Contraction of Electrically Paced Neonatal Rat Ventricular Myocytes in Culture

Abstract: There is evidence that infarcted myocardium contributes to the increase of cell-free DNA levels (cfDNA). We studied the effect of different human DNA fragments on the rate of contraction of the electrically paced neonatal rat ventricular myocytes in culture (spontaneously hypertensive line SHR). AT-rich fragments of the human satellite 3 tandem repeat (1q12 region) at a concentration of 1 ng/mL increase the frequency of cardiomyocyte contractions by 2-2.5 times. GC-rich fragments of the rDNA at 0.5 ng/mL decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 12 publications
0
23
0
5
Order By: Relevance
“…Все перечисленные события связаны с увеличением активности индуцибельной NO-синтазы в КМК [46,47]. В нашем опыте инкубирование КМК с лигандами TLR9 (ДНК E. coli или CpG-богатые фрагменты плазмидной ДНК) также сопровождалось уменьшением частоты сокращений КМК [48]. При концентрации лиганда в среде более 50 нг/мл (24 часа) мы наблюдали полное блокирование сократительной активности КМК.…”
Section: определение концентрации метаболита No -нитрит-иона по методunclassified
“…Все перечисленные события связаны с увеличением активности индуцибельной NO-синтазы в КМК [46,47]. В нашем опыте инкубирование КМК с лигандами TLR9 (ДНК E. coli или CpG-богатые фрагменты плазмидной ДНК) также сопровождалось уменьшением частоты сокращений КМК [48]. При концентрации лиганда в среде более 50 нг/мл (24 часа) мы наблюдали полное блокирование сократительной активности КМК.…”
Section: определение концентрации метаболита No -нитрит-иона по методunclassified
“…Внеклеточная ДНК (вкДНК) -это продукт деградации погибших в результате некроза или апоптоза клеток организма [6,7], хотя существует предположение, что вкДНК также может выделяться живыми клетками (метаболическая ДНК) [8]. Показано, что вкДНК отличается по составу от геномной ДНК: вкДНК значительно обогащена GC-парами [5,9,10], аналогично бактериальной ДНК. Так, содержание GC-богатой (GC-ДНК) умеренно повторяющейся последовательности генома -транскрибируемой области рибосомного повтора (ТОрДНК) -в составе вкДНК в несколько раз превышает содержание этого повтора в ДНК клеточных ядер [5,9,10].…”
unclassified
“…Показано, что вкДНК отличается по составу от геномной ДНК: вкДНК значительно обогащена GC-парами [5,9,10], аналогично бактериальной ДНК. Так, содержание GC-богатой (GC-ДНК) умеренно повторяющейся последовательности генома -транскрибируемой области рибосомного повтора (ТОрДНК) -в составе вкДНК в несколько раз превышает содержание этого повтора в ДНК клеточных ядер [5,9,10]. В то же время в составе вкДНК отмечается снижение содержания АТ-богатых последовательностей [11].…”
unclassified
See 1 more Smart Citation
“…Although apoptosis and necrosis are considered to be the main processes for producing cirDNA, numerous studies have demonstrated that cirDNA can also be derived from active cellular release mechanisms [7][8][9][10][11][12]. Further examination showed that actively released DNA is often associated with RNA and a lipid-protein complex, can translocate to neighboring or remote parts of the body, enter target cells, and alter their biology [12][13][14][15][16][17][18]. In the following years, it became clear that the active release and uptake of nucleic acids are a characteristic shared by all organisms and cell types [19].…”
Section: Introductionmentioning
confidence: 99%